2023
DOI: 10.1093/infdis/jiad012
|View full text |Cite
|
Sign up to set email alerts
|

Underascertainment of Respiratory Syncytial Virus Infection in Adults Due to Diagnostic Testing Limitations: A Systematic Literature Review and Meta-analysis

Abstract: Background Most observational population-based studies identify RSV by nasal/nasopharyngeal swab RT-PCR only. We conducted a systematic review and meta-analyses to quantify specimen and diagnostic testing-based under-ascertainment of adult RSV infection. Methods EMBASE, PubMed and Web of Science were searched (Jan2000–Dec2021) for studies including adults using/comparing >1 RSV testing approach. We quantified test perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 47 publications
3
43
1
Order By: Relevance
“…We have based this work on regression model estimates [which are not so dependent on high levels of RSV testing] to increase the comparability of the Stage 1 estimates [41] and to limit the risk of underestimating the RSV disease burden in adults (as there is less testing in this age group) [13]. Considering that the review of the literature found no eligible recent studies, there is a need for more data from more countries to generate improved estimates with less uncertainty as the uncertainty intervals given here are falsely narrow and do not capture all sources of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have based this work on regression model estimates [which are not so dependent on high levels of RSV testing] to increase the comparability of the Stage 1 estimates [41] and to limit the risk of underestimating the RSV disease burden in adults (as there is less testing in this age group) [13]. Considering that the review of the literature found no eligible recent studies, there is a need for more data from more countries to generate improved estimates with less uncertainty as the uncertainty intervals given here are falsely narrow and do not capture all sources of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported varying estimates of the incidence of RSV infections in hospitalised adults [5, 11, 12]. Estimating the incidence of RSV infection in hospitalised adults remains challenging as there are no dedicated RSV surveillance systems, RSV is not routinely screened for in patients with an ARI and only the more severe cases are commonly diagnosed [13]. RSV-associated mortality among older adults is reportedly substantial and comparable to influenza [14] with the majority of deaths occurring among persons aged ≥60 years [8].…”
Section: Introductionmentioning
confidence: 99%
“…We calculated the proportion of detection by each possible combination of testing approach(es) compared with the gold standard, as reported by Falsey and colleagues [ 9 ] (assuming that any positives by any of the three methods—PCR, culture and paired serology—were true positives); as a result, the detection proportion should range from 0 (lowest sensitivity) to 1 (perfect sensitivity). We also calculated the proportion of detection by rapid antigen testing compared with the gold standard through a systematic review of RSV diagnostic accuracy comparison [ 10 ]. As the second step, we focused on adjusting for clinical specimen conditioning on testing method.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a study that compared different diagnostic tests of RSV among adults found that only half of the RSV cases confirmed by reverse transcription polymerase chain reaction (RT-PCR) had a positive viral culture result [ 9 ]. Furthermore, a growing body of literature recently summarised in a systematic review and meta-analysis suggests that use of nasopharyngeal (NP) or nasal swabs alone to identify RSV infection yields downwardly biased estimates of RSV disease rates [ 10 ]. Compared to NP/nasal swab alone, RSV detection increased by 52% when adding RT-PCR of sputum, 28% when adding RT-PCR of oropharyngeal swabs, and 42% when adding serology testing of paired specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a retrospective cohort study from Eastern Finland in 2017–2018 showed that RSV-infected patients were older and had an increased risk of hospitalization and mortality in comparison to influenza virus-infected adults [26 ▪▪ ]. The level of RSV infection in adults and older adults may also be underestimated due to limitations in diagnostic testing, a situation that could be alleviated by the collection and testing of three or more specimen types from patients [27]. The burden of RSV-infection in healthy term infants has also been recently assessed in a prospective birth cohort study performed in five locations in Europe [28].…”
Section: Vaccinesmentioning
confidence: 99%